PENGARUH TEKNIK PERMAINAN MENYUSUN KATA PADA MATA PELAJARAN BAHASA INDONESIA TERHADAP KEMAMPUAN MEMBACA SISWA KELAS I SDN 24 GELUMBANG - Rini Andika; Djunaidi; Hetilaniar (STKIP Subang, 2023)
The background of one of the subjects that must be given in elementary schools is Indonesian.The scope of learning Indonesian in elementary schools includes 4 (four) components of language skills, namely listening / listening, reading, writing, and speaking. The above problem makes the author feel the need to conduct a study entitled